The contagion and treatment of syphilis during the Virreinate in the story «Las orejas del alcalde» - Antayhua Saavedra, Cindy Dayana (2022)
In this article, we will analyze the story «Las orejas del alcalde», by Ricardo Palma, from a medical point of view, since one of the most outstanding characteristics of the character known as Diego de Esquivel, mayor, is that he is a womanizing man without a stable relationship. We will observe that since the 16th century, sexually transmitted diseases have spread, which are predominantly spread by carnal contact and even by saliva. The causes and consequences of this disease on health will also be explained. Finally, the promotion of sexual health and prevention of syphilis, as well as its treatment, will be discussed.